2000
DOI: 10.1074/jbc.m000300200
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal RG Dipeptide Repeats of the Spliceosomal Sm Proteins D1 and D3 Contain Symmetrical Dimethylarginines, Which Form a Major B-cell Epitope for Anti-Sm Autoantibodies

Abstract: The Sm proteins B/B, D1, D2, D3, E, F, and G are components of the small nuclear ribonucleoproteins U1, U2, U4/U6, and U5 that are essential for the splicing of pre-mRNAs in eukaryotes. D1 and D3 are among the most common antigens recognized by anti-Sm autoantibodies, an autoantibody population found exclusively in patients afflicted with systemic lupus erythematosus. Here we demonstrate by protein sequencing and mass spectrometry that all arginines in the C-terminal arginine-glycine (RG) dipeptide repeats of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
221
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 272 publications
(232 citation statements)
references
References 57 publications
8
221
1
2
Order By: Relevance
“…The data from the (GR)-repeat portion of the D3 polypeptide, its similarity to D1, and the cross-reactivity of affinity-purified anti-D3 Abs with this region of D1 seem to support the theory of crossreactivity explaining the appearance of some autoantibodies. An additional group has shown that this same region of Sm D1 is antigenic when the alternating arginines are dimethylated (35). Interestingly, this posttranslational modification may not be absolutely required for antigenicity of these sequences, as has been shown by this and other works (8,(33)(34).…”
Section: Discussionmentioning
confidence: 55%
“…The data from the (GR)-repeat portion of the D3 polypeptide, its similarity to D1, and the cross-reactivity of affinity-purified anti-D3 Abs with this region of D1 seem to support the theory of crossreactivity explaining the appearance of some autoantibodies. An additional group has shown that this same region of Sm D1 is antigenic when the alternating arginines are dimethylated (35). Interestingly, this posttranslational modification may not be absolutely required for antigenicity of these sequences, as has been shown by this and other works (8,(33)(34).…”
Section: Discussionmentioning
confidence: 55%
“…Anti-Sm antibodies, in vertebrates, are known to react with the Sm proteins B/BЈ, D1, and D3 (Lehmeier et al 1990), which contain symmetrical dimethyl arginine modifications on their RG-rich C-terminal tails (Brahms et al 2000(Brahms et al , 2001. However, by using the Y12 antibody, we could only detect the B/BЈ and D1 proteins, not D3, on Western blots of nuclear extracts from human 293-T cells (Fig.…”
Section: Drosophila Lsm10 and Lsm11 Interact With Each Other And Withmentioning
confidence: 75%
“…In addition, the SmD1 and SmD3 lack the C-terminal RG dipeptide repeats of the human homologues (30). The arginine in this domain is methylated in the mammalian protein, constituting an important determinant of the Sm epitope (33). The lack of these modifications on the trypanosome proteins may partly explain why the trypanosome Sm proteins are not recognized by the Sm antibodies (28).…”
mentioning
confidence: 94%